Lipotoxic stress alters the membrane lipid profile of extracellular vesicles released by Huh-7 hepatocarcinoma cells - Sandra Buratta (Nature Portfolio, 2021)
Abstract Extracellular vesicles (EVs) are well-known mediators in intercellular communication playing pivotal roles in promoting liver inflammation and fibrosis, events associated to hepatic lipotoxicity caused by saturated free fatty acid overloading. However, despite the importance of lipids in EV membrane architecture which, in turn, affects EV biophysical and biological properties, little is known about the lipid asset of EVs released under these conditions. Here, we analyzed phospholipid profile alterations of EVs released by hepatocarcinoma Huh-7 cells under increased membrane lipid saturation induced by supplementation with saturated fatty acid palmitate or Δ9 desaturase inhibition, using oleate, a nontoxic monounsaturated fatty acid, as control. As an increase of membrane lipid saturation induces endoplasmic reticulum (ER) stress, we also analyzed phospholipid rearrangements in EVs released by Huh-7 cells treated with thapsigargin, a conventional ER stress inducer. Results demonstrate that lipotoxic and/or ER stress conditions induced rearrangements not only into cell membrane phospholipids but also into the released EVs. Thus, cell membrane saturation level and/or ER stress are crucial to determine which lipids are discarded via EVs and EV lipid cargos might be useful to discriminate hepatic lipid overloading and ER stress.